2010
DOI: 10.1164/rccm.200804-625oc
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule Epidermal Growth Factor 8 Attenuates Acute Lung Injury in Mice after Intestinal Ischemia and Reperfusion

Abstract: Rationale: Milk fat globule epidermal growth factor 8 (MFG-E8) is a potent opsonin for the clearance of apoptotic cells and is produced by mononuclear cells of immune competent organs including the spleen and lungs. It attenuates chronic and acute inflammation such as autoimmune glomerulonephritis and bacterial sepsis by enhancing apoptotic cell clearance. Ischemia-reperfusion (I/R) injury of the gut results in severe inflammation, apoptosis, and remote organ damage, including acute lung injury (ALI). Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 44 publications
8
110
0
Order By: Relevance
“…We have previously found no differences in lung inflammation in bleomycin-treated Mfge8 −/− mice (29). Other studies have shown that Mfge8 −/− mice develop exaggerated lung inflammation after intratracheal LPS instillation or after reperfusion injury secondary to intestinal ischemia (42,43). Given the important role of the immune system in asthma, we were curious to determine whether there would be differences in airway inflammation in Ova-challenged Mfge8 −/− mice.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously found no differences in lung inflammation in bleomycin-treated Mfge8 −/− mice (29). Other studies have shown that Mfge8 −/− mice develop exaggerated lung inflammation after intratracheal LPS instillation or after reperfusion injury secondary to intestinal ischemia (42,43). Given the important role of the immune system in asthma, we were curious to determine whether there would be differences in airway inflammation in Ova-challenged Mfge8 −/− mice.…”
Section: Discussionmentioning
confidence: 94%
“…In pathophysiological conditions such as sepsis, 34 I/R injury, 35,36 ulcerative colitis 37,38 and atherosclerosis, 39 a significant downregulation of MFG-E8 was reported (Figure 1). For instance, tissue concentrations of MFG-E8 in septic rats have been described to decrease while the number of apoptotic cells increased simultaneously.…”
Section: Role In Inflammatory Diseasesmentioning
confidence: 94%
“…For example, treatment with recombinant MFG-E8 accelerated mucosal healing in various models of I/R injury models as well as in septic mice and mice with radiation-induced intestinal mucosal damage. 36,[44][45][46][47][48] In most cases, the increased clearance of apoptotic cells, the reduced inflammation and an increase in epithelial cell proliferation have been described as underlying mechanisms. Importantly, treatment with recombinant MFG-E8 has been shown to both, prevent colitis when given before disease onset and ameliorate disease burden when given once the full-blown disease was established.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…28 Also, Chogle et al 29 demonstrated that MFG-E8KO mice develop more severe crypt-epithelial injury during the onset of DSSinduced acute colitis, 29 whereas a recent study revealed the anti-inflammatory effects of recombinant MFG-E8 protein in a mouse model of ischemia and reperfusion-induced intestinal injuries. 16 Thus, a beneficial effect of MFG-E8 on downregulation of inflammation has been shown. In this study, we demonstrated its anti-inflammatory function via modulation of butyric acid during acute colitis.…”
Section: Butyric Acid Enema During Acute Phase Of Experimental Colitimentioning
confidence: 97%
“…12,13 Several studies have revealed that MFG-E8 has important roles in the pathogenesis of inflammatory and autoimmune diseases, as well as sepsis, atherosclerosis, and neurodegenerative disorders, [14][15][16] whereas recent findings have also revealed that MFG-E8 mRNA and protein levels were lower in inflamed intestinal specimens obtained during biopsies from patients with ulcerative colitis (UC) as compared with control biopsy specimens. 17 Those features have been suggested to be dependent not only on enhanced clearance of apoptotic cells but also on various novel molecular mechanisms.…”
mentioning
confidence: 99%